An Efficient Rh/O2 Catalytic System for Oxidative C–H Activation/Annulation: Evidence for Rh(I) to Rh(III) Oxidation by Molecular Oxygen - Zhang, Guoying; Yang, Lei; Wang, Yanyu; Xie, Yinjun; Huang, Hanmin (Journal of the American Chemical Society, 2013)
A novel and efficient Rh/O2 catalytic system has been developed and shown to catalyze highly efficient oxidative C–H activation/annulation reactions, producing a broad range of isoquinolinium salts with high turnover numbers (up to 740). Mechanistic studies provided strong evidence of facile oxidation of Rh(I) to Rh(III) by molecular oxygen facilitated by acid.